Melatonin Treatment for Sleep Disorders in Parkinson's Disease: A Meta-Analysis and Systematic Review - Ma, Hongxia; Yan, Junqiang; Sun, Wenjie; Jiang, Menghan; Zhang, Yongjiang (Frontiers in Aging Neuroscience, 2022)
Objective: The efficacy of melatonin on sleep disorders in Parkinson's disease (PD) is still unclear. The purpose of this study is to investigate the efficacy of melatonin on sleep disorders in PD by summarizing evidence from randomized clinical trials (RCTs). Methods: PubMed, Cochrane Library, EMBASE, and Web of science were searched until 20 August 2021. Results were analyzed using Review Manager 5. 2 software. We used the software of trial sequential analysis (TSA) to avoid false-positive results caused by random errors. Results: We included 7 studies to conduct this systematic review and meta-analysis. Results of the meta-analysis showed that compared with placebo, the subjective sleep quality of PD patients had a significant improvement after receiving melatonin treatment (MD = -2. 19, 95% CI: -3. 53 to -0. 86, P = 0. 001). In this systematic review, we qualitatively analyzed the efficacy of melatonin on the objective sleep quality of PD, and results showed that melatonin exerts a positive effect with good safety and tolerability. However, there isn’t significant improvement in excessive daytime sleepiness assessed by the Epworth Sleepiness Scale (ESS). Conclusion: We found that melatonin can significantly improve the subjective and objective sleep quality of PD patients with good safety and tolerability. Melatonin may be a promising treatment for insomnia in PD patients.